2018
DOI: 10.1007/s13280-018-1088-x
|View full text |Cite
|
Sign up to set email alerts
|

Recreational boating degrades vegetation important for fish recruitment

Abstract: Recreational boating increases globally and associated moorings are often placed in vegetated habitats important for fish recruitment. Meanwhile, assessments of the effects of boating on vegetation, and potential effects on associated fish assemblages are rare. Here, we analysed (i) the effect of small-boat marinas on vegetation structure, and (ii) juvenile fish abundance in relation to vegetation cover in shallow wave-sheltered coastal inlets. We found marinas to have lower vegetation cover and height, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 43 publications
(81 reference statements)
2
36
1
Order By: Relevance
“…The Baltic Sea is one of the most heavily impacted marine systems in the world [18], and coastal areas are hot-spots for anthropogenic impact [47,48]. In contrast to the offshore Baltic Sea, where the fish community is mainly impacted by commercial fishing, eutrophication, and climate [49], coastal fish communities are also increasingly impacted by habitat degradation, recreational fishing, boating, interactions in the food web, and hazardous substances [50][51][52][53][54][55]. To that end, as most coastal fish species have local population structures in combination with the strong environmental gradients in the Baltic Sea, the major impacting pressures influencing coastal predatory fish populations vary between areas and regions [28,29].…”
Section: Impacts On Coastal Predatory Fish Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Baltic Sea is one of the most heavily impacted marine systems in the world [18], and coastal areas are hot-spots for anthropogenic impact [47,48]. In contrast to the offshore Baltic Sea, where the fish community is mainly impacted by commercial fishing, eutrophication, and climate [49], coastal fish communities are also increasingly impacted by habitat degradation, recreational fishing, boating, interactions in the food web, and hazardous substances [50][51][52][53][54][55]. To that end, as most coastal fish species have local population structures in combination with the strong environmental gradients in the Baltic Sea, the major impacting pressures influencing coastal predatory fish populations vary between areas and regions [28,29].…”
Section: Impacts On Coastal Predatory Fish Populationsmentioning
confidence: 99%
“…In addition, predatory fish such as pike and perch utilize coastal tributaries and streams for spawning and recruitment along many coastal areas in the Baltic Sea [57,64,65]. However, both the quality and availability of essential habitats for predatory fish in coastal areas, tributaries, and streams have deteriorated during decades and centuries as a result of intense physical exploitation of [66,67], as well as boating in [55,68], the habitats.…”
Section: Impacts On Coastal Predatory Fish Populationsmentioning
confidence: 99%
“…The elevated nutrient conditions increase the production of ephemeral primary producers, such as phytoplankton and filamentous algae, which leads to shading and impaired growth conditions for larger, habitat-forming vegetation, such as bladderwrack and perennial macrophytes (Berger et al 2004;Austin et al 2017), and subsequent deterioration of associated ecosystem services (Rönnbäck et al 2007). For example, many fish species rely on the habitats shaped by structurally complex vegetation during early life stages, and therefore degradation or loss of vegetated habitats is associated with negative effects on population abundances (Mumby et al 2004;Seitz et al 2013;Hansen et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several studies indicate that the ability of submerged vegetation to reduce turbidity is related to the abundance or areal extent of vegetation (Orth et al 1999;Moore 2004;Austin et al 2017). Moreover, the abundance of macroinvertebrates (Diehl and Kornijów 1998;Attrill et al 2000), as well as juvenile fish (Hansen et al 2018;Kraufvelin et al 2018), has been shown to increase with vegetation abundance. Hence, vegetation decline caused by boating activities may substantially degrade the habitat quality provided by vegetation in the otherwise flat seascape of soft bottoms.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the number of berths may be a crude measure of boating intensity. However, a recent study by Hansen et al (2018) found that the abundance of rooted vegetation decreased significantly with the density of berths in Baltic Sea coastal bays, indicating that such relationship may exist-at least for rooted species.…”
Section: Why Do the Effects Vary?mentioning
confidence: 95%